Metal artefact reduction algorithm for correction of bone biopsy needle artefact in paediatric C-arm CT images: a qualitative and quantitative assessment. Issue 9 (September 2016) - Shellikeri, S.; Girard, E.; Setser, R.; Bao, J.; Cahill, A.M.
Highlights: Evaluation of Metal Artefact Reduction algorithm for C-arm CT biopsy needle artefact. MAR-corrected images demonstrated improved image quality. Significant image-noise reduction observed in the needle vicinity in patient group. MAR algorithm provides better visualization of needle and surrounding soft tissue. MAR can potentially improve physician's confidence in needle tip placement.